2021
DOI: 10.1186/s12888-021-03194-2
|View full text |Cite
|
Sign up to set email alerts
|

Severe sleep disturbance is associated with executive function impairment in patients with first-episode, treatment-naïve major depressive disorders

Abstract: Background Sleep disturbance and executive function impairment are common in patients with major depressive disorder (MDD), though the relationship between the two remains unclear. We investigated this association in first-episode, treatment-naïve patients with MDD. Methods We analyzed data from 242 patients with MDD. We divided the patients into 2 groups based on sleep disturbance severity and compared the executive function odds ratios between th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Similarly, SCZ and the manic phase of BP share the reduced need for sleep [ 103 , 104 , 105 , 106 ]. In MDD and during the depressive phase of BP, patients present both hypersomnia and severe insomnia [ 107 , 108 , 109 , 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, SCZ and the manic phase of BP share the reduced need for sleep [ 103 , 104 , 105 , 106 ]. In MDD and during the depressive phase of BP, patients present both hypersomnia and severe insomnia [ 107 , 108 , 109 , 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…These disruptions manifest as irregular sleep-wake cycles, diurnal mood variations, seasonal fluctuations, changes in eating habits, and alterations in daily social functioning [ 3 ]. Studies have shown a close correlation between circadian rhythm disruptions and the onset, symptomatology, recurrence, and prognosis of MDD [ 4 ]. The disturbance of circadian rhythms represents a significant clinical feature of MDD [ 5 ].…”
Section: Introductionmentioning
confidence: 99%